Equity, access and allocation: discrimination in an irrigation project - Lele, S.N.; Patil, R.K. (2006)
Rising population and over-exploitation of groundwater for irrigation has aggravated conflict among farmers located at the upper reaches and the tail end of the Palkhed canal system of the upper Godavari project of Maharashtra. The formation of water users' association did alleviate the conflict to some degree, but there continues to be disagreement between the government's water department and the WUAs on the terms of allocation and other measures. - Reproduced.
Keywords: Irrigation